Van der Knaap disease: a case report - Ramzan, Younus; Bukhari, Syed Tariq Ahmed; Ashraf, Mohd; Kazime, Umeair Farooq; Wani, Asma (International Journal of Contemporary Pediatrics, 2020)
Van der Knaap disease or megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare autosomal recessive degenerative disorder characterized by megalocephaly, cerebral leukoencephalopathy, and motor deterioration. Most cases reported with this disease are from our country India, belong to Agarwal community, who have high rates of consanguinity. We report a 4 and 1/2year old boy, with a history of delayed motor milestones, ataxia, increasing head circumference and abnormal body movements, who is belonging to the Bhat family of Handwara town of Kupwara district of Jammu and Kashmir, India.